2010
DOI: 10.1002/eji.201040841
|View full text |Cite
|
Sign up to set email alerts
|

Selection of escape mutant by HLA‐C‐restricted HIV‐1 Pol‐specific cytotoxic T lymphocytes carrying strong ability to suppress HIV‐1 replication

Abstract: HIV‐1 mutants escaping from HLA‐A‐ or HLA‐B‐restricted CTL have been well studied, but those from HLA‐C‐restricted CTL have not. Therefore we investigated the ability of HLA‐C‐restricted CTL to select HIV‐1 escape mutants. In the present study, we identified two novel HLA‐Cw*1202‐restricted Pol‐specific CTL epitopes (Pol328‐9 and Pol463‐10). CTL specific for these epitopes were detected in 25–40% of chronically HIV‐1‐infected HLA‐Cw*1202+ individuals and had strong abilities to kill HIV‐1‐infected cells and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 45 publications
1
34
1
Order By: Relevance
“…Since HLA-C*12:02 and HLA-B*52:01 have very high linkage disequilibrium in Japan, it is likely that HLA-B*52:01-associated mutations can be escape mutations from HLA-C*12:02-restricted CTLs. We previously showed that IY10 (ILKEPVHGVY) is an HLA-C*12:02-restricted epitope (36). However, bulk T cells induced by IY11 recognized the IY11 peptide more than IY10 (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Since HLA-C*12:02 and HLA-B*52:01 have very high linkage disequilibrium in Japan, it is likely that HLA-B*52:01-associated mutations can be escape mutations from HLA-C*12:02-restricted CTLs. We previously showed that IY10 (ILKEPVHGVY) is an HLA-C*12:02-restricted epitope (36). However, bulk T cells induced by IY11 recognized the IY11 peptide more than IY10 (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…C1R cells expressing HLA-B*52:01 or HLA-C*12:02 and 721.221 cells expressing CD4 molecules as well as HLA-B*52:01 or HLA-C*12:02 were previously generated (36,38,39) and maintained in RPMI medium with 10% fetal calf serum (FCS) and 0.15 mg/ml hygromycin B.…”
Section: Methodsmentioning
confidence: 99%
“…The Y181C mutation is selected in patients receiving NVP, etravirine (ETR), and ripivirine (RPV) and reduces susceptibility to these drugs and EFV, whereas Y181I/V mutations are selected by NVP and ETR and cause resistance to these drugs and to RPV (16)(17)(18)(19)(20)(21)(22)(23). These 3 RT181 mutations are located in previously reported epitopes, HLA-A*02:01-restricted IV10 (RT 180 -189), HLA-B*35:01-restricted NY9 (RT 175-183), and HLA-C*12:02-restricted KY9 (RT 173-181), in HIV-1 subtype B (24)(25)(26). We investigated here the effect of the RT181 mutations on epitope recognition by CTLs specific for 3 different epitopes in HIV-1 subtype B and subtype A/E infections and the accumulation of these mutations in treatment-naive Japanese and Vietnamese to clarify the effect of these NNRTI-resistance mutations on immune control of HIV-1.…”
mentioning
confidence: 81%
“…C1R-A*0201, -B*3501, and -C*1202, 721.221-CD4-B*3501 and -C*1202, and RMA-S-B*3501 were previously generated (25)(26)(27)(28)(29). 721.221-CD4-A*0201 and RMA-S-A*0201 were obtained by transfecting 721.221-CD4 cells and RMA-S cells, respectively, with the HLA-A*02:01 gene.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that some escape mutations affect replication capacity and that HIV-1 containing such mutations reverts to WT in individuals not carrying HLA class I restriction alleles (23,32). We previously showed that the 3R mutation does not affect replication capacity when 2 T cell lines are used in an assay measuring it (46).…”
Section: Figmentioning
confidence: 98%